2019
DOI: 10.35940/ijitee.l3984.1081219
|View full text |Cite
|
Sign up to set email alerts
|

The Awareness of Blind Spot Area in Heavy Goods Vehicle (HGV)

Abstract: This paper is to demonstrate the awareness of blind spot area in heavy goods vehicles (HGV) towards the road user. A blind spot is an area or zone that cannot be directly observe by the driver. Usually, the weaknesses in the blind spot area resulted in accident between the vehicle as many drivers did not alert or have awareness on the blind spot area especially in heavy goods vehicle. The objective of this paper is to identify the awareness on the blind spot area in heavy goods vehicles to the road users. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Truck driver visibility is impeded by the size of the vehicle. Trucks have greater blind spot areas than passenger vehicles, and impaired visibility in these areas increases crash risk [16]. A blind spot area is defined as an area around the perimeter of the vehicle that cannot be seen by the driver using standard windows or mirrors [17].…”
Section: Performance Limitations Of Trucks and Associated Road Safety Risksmentioning
confidence: 99%
See 3 more Smart Citations
“…Truck driver visibility is impeded by the size of the vehicle. Trucks have greater blind spot areas than passenger vehicles, and impaired visibility in these areas increases crash risk [16]. A blind spot area is defined as an area around the perimeter of the vehicle that cannot be seen by the driver using standard windows or mirrors [17].…”
Section: Performance Limitations Of Trucks and Associated Road Safety Risksmentioning
confidence: 99%
“…Truck drivers have four main blind spot areas: immediately in front of the truck; behind the door on the driver side of the vehicle, the length of the passenger side of the vehicle, and directly behind the truck. To minimise crash risk associated with lane changing or merging, other motorists need to avoid driving in these blind spot areas [16] and need to be mindful of the intentions of truck drivers if they are situated in a truck blind spot. Although there is little research into motorists' knowledge of truck and heavy vehicle blind spots, a study conducted in Malaysia found that when questioned on their knowledge of the location of truck blind spots, less than half of the 100 surveyed respondents were aware of blind spot locations to the front, left and right perimeters of a heavy vehicle [16].…”
Section: Performance Limitations Of Trucks and Associated Road Safety Risksmentioning
confidence: 99%
See 2 more Smart Citations